Tinjauan Hukum Pencemaran Nama Baik Terhadap Pejabat Negara: Kajian atas Putusan Hakim Nomor 341/Pid.B/2014/PN.SGM - Orin Gusta Andini (Wacana Hukum, 2019)
Since 2009 until now there have been 30 cases tried by the District Courts in Indonesia using Article 27 paragraph (3) of Law Number 19 Year 2016 concerning Amendments to Law Number 11 Year 2008 concerning Information and Electronic Transactions. These various cases gave rise to opinions from some people who considered the articles of defamation offenses contrary to the spirit of reform which upheld the freedom of opinion and expression. This type of research is normative legal research. Normative legal research prioritizes library research with a focus on studies of legal principles, legal systematics, legal synchronization and legal history, this research is also descriptive. This study concluded that the crime of reputation after the decision of the Constitutional Court Number 50 / PUU-VI / 2008, Decision of the Constitutional Court Number 2 / PUU-VII / 2009, Decision of the Constitutional Court Number 5 / PUU-VIII / 2010, Decision of the Constitutional Court Number 31 / PUU-XIII / 2015 and Constitutional Court Decision Number 76 / PUU-XV / 2017 concerning Testing of Law Number 19 Year 2016 concerning Amendment to Law Number 11 Year 2008 concerning Information and Electronic Transactions of the Constitution of the Republic of Indonesia Year 1945 is regulated in detail with one of the points, namely making changes in Article 27 paragraph (3) of the ITE Law and reducing criminal threats in 2 (two) provisions.